The Barthel Index predicts surgical textbook outcomes following hepatectomy for elderly patients with hepatocellular carcinoma: A multicenter cohort study - Yang, Tian; Liu, Da-Qun; Qiu, Wei; Fan, Zhong-Qi; Sun, Li-Yang; Wang, Nan-Ya; Wang, Hong; Yang, Yi-Fan; Li, Jie; Zhou, Ya-Hao; Chen, Ting-Hao; Wang, Xian-Ming; et al. (The American journal of surgery, 2024)
The burgeoning demand for hepatectomy in elderly patients with hepatocellular carcinoma (HCC) necessitates improved perioperative care. Geriatric populations frequently experience functional decline and frailty, predisposing them to adverse postoperative outcomes. The Barthel Index serves as a reliable measure for assessing functional capacity, and this study evaluates its impact on surgical textbook outcomes (TOs) in elderly HCC patients. A multicenter retrospective cohort study analyzed elderly patients (≥70 years) following hepatectomy for HCC between 2013 and 2021. Utilizing a Barthel Index cut-off value of 85, patients were divided into two groups: with and without preoperative functional decline and frailty. The primary outcome was the rate of TO, encompassing seven criteria. TO rates were compared between groups, and multivariate logistic regression analyses identified independent risks for achieving TOs. Of 497 elderly patients, 157 (31.6 ​%) exhibited preoperative functional decline and frailty (Barthel Index score <85). The overall TO rate was 58.6 ​%. Patients with preoperative Barthel Index score <85 had significantly lower TO rates compared to patients with score ≥85 (29.3 ​% vs. 72.1 ​%, P ​< ​0.001). Multivariate analysis revealed preoperative Barthel Index score <85 as an independent risk for achieving TO (odds ratio 3.413, 95 ​% confidence interval 1.879–6.198, P ​< ​0.001). Comparable results were observed in the subgroups of patients undergoing open and laparoscopic hepatectomy. Preoperative Barthel Index-based assessment of functional decline and frailty significantly predicts TOs following hepatectomy in elderly HCC patients, enabling identification of high-risk patients and informing preoperative management and postoperative care within geriatric oncology. [Display omitted] •Only 2 in 5 elderly patients achieved Textbook Outcome following hepatectomy for hepatocellular carcinoma.•Preoperative Barthel Index-based assessment of functional decline and frailty predicts Textbook Outcome following hepatocellular carcinoma resection.•The association between Barthel index and Textbook Outcomes was consistent across surgical modalities (open or laparoscopic hepatectomy).